Pendampingan Dalam Penggunaan Media Digital Untuk Pembelajaran Pendidikan Agama Islam Di Desa Bonder Kecamatan Praya Barat - Hadlun, Hadlun; Ala Purnawati; Dedi Alfarizi; Dian Sholehatin (Jurnal Pengabdian Masyarakat Sains Indonesia, 2021)
Teacher assistance in using digital media in Islamic Religious Education (PAI) learning in Bonder Village is very much needed, especially technological readiness both in terms of teachers as educators, parents' readiness in providing facilities to students at home, and students' readiness as learning implementers must be prepared in advance so that learning can run smoothly. The purpose of community service activities is to provide assistance to partners in using digital media for Islamic Religious Education learning in order to optimize the learning process. The steps used to overcome partners problems include: 1) socialization related to the assistance program; 2) training and practice in using digital-based learning media; 3) assistance; and 4) monitoring activities. The results of this assistance show an increase in partner competence in using digital media, as well as an increase in partner interest and understanding of the use of digital media in PAI learning which is delivered through training. This article also evaluates the challenges faced during the assistance process and provides recommendations for further implementation in other villages. From the community service activities that have been carried out, it is known that the enthusiasm of partners in participating in this assistance shows high enthusiasm. This can be seen from the strong will of the partners to understand and practice using digital media in learning, especially Islamic Religious Education (PAI).